GLI3 Is Associated With Neuronal Differentiation in SHH-Activated and WNT-Activated Medulloblastoma. Issue 2 (18th January 2021) - Natsumeda, Manabu; Miyahara, Hiroaki; Yoshimura, Junichi; Nakata, Satoshi; Nozawa, Takanori; Ito, Junko; Kanemaru, Yu; Watanabe, Jun; Tsukamoto, Yoshihiro; Okada, Masayasu; Oishi, Makoto; Hirato, Junko; et al.
Abstract: Glioma-associated oncogene homolog 3 (GLI3), whose main function is to inhibit GLI1, has been associated with neuronal differentiation in medulloblastoma. However, it is not clear what molecular subtype(s) show increased GLI3 expression. GLI3 levels were assessed by immunohistochemistry in 2 independent cohorts, including a total of 88 cases, and found to be high in both WNT- and SHH-activated medulloblastoma. Analysis of bulk mRNA expression data and single cell RNA sequencing studies confirmed that GLI1 and GLI3 are highly expressed in SHH-activated medulloblastoma, whereas GLI3 but not GLI1 is highly expressed in WNT-activated medulloblastoma. Immunohistochemical analysis has shown that GLI3 is expressed inside the neuronal differentiated nodules of SHH-activated medulloblastoma, whereas GLI1/2 are expressed in desmoplastic areas. In contrast, GLI3 is diffusely expressed in WNT-activated medulloblastoma, whereas GLI1 is suppressed. Our data suggest that GLI3 may be a master regulator of neuronal differentiation and morphology in these subgroups.